PENGARUH KUALITAS DAN HARGA PRODUK TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH WORD OF MOUTH (STUDI KASUS RUMAH TENUN PUTA DINO TIDORE) - Fabanyo, Rohani; Haji, Sulfi Abdul; Hi. Yusuf, Ibnu Sina (Jurnal MS, 2023)
ABSTRACT Objective: This study aims to determine the influence of product quality and price on purchasing decisions mediated by word of mouth in the case of the Puta Dino Tidore weaving house. Methodology: The population in this study were all visitors to the Puta Dino Tidore weaving house. The number of samples in this research is the number of indicators/items x 7, namely 15 x 7 = 105 respondents Finding: The partial hypothesis and simultaneous hypothesis are accepted, because the alpha value is smaller than 5%, except for the first hypothesis there is no significant effect. Conclusion: The results of this research indicate that product quality does not have a significant effect on purchasing decisions; price has a significant effect on purchasing decisions; product quality has a significant effect on word of mouth promotion; price has a significant effect on word of mouth promotion; Word of Mouth has a significant influence on purchasing decisions. Product quality has a significant influence on purchasing decisions through word of mouth mediation. Price has a significant influence on purchasing decisions through word of mouth. Â 